Multiple linear regression analysis and lagrange polynomial on pyrolysis process of coconut shell waste producing solid biochar - Rosdanelli Hasibuan; Rita Sundari; Hans Martua Pardede; Vikram Alexander; Juliza Hidayati (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Coconut shell waste has generated environmental problems in Indonesia. Due to fossil fuel shortage, coconut shell waste has been advantaged as an energy source to replace the fossil energy. A pyrolysis technique has been used to crack coconut shell waste into charcoal or solid biochar. An MLR (Multiple Linear Regression) analysis and Lagrange polynomial interpolation has been applied to the pyrolysis process related to pyrolysis temperature and time-affected charcoal characteristics. This type of analysis often used for process optimization. The charcoal characteristics are investigated in terms of their yield, water content, ash content, volatile matter, and calorific value. The experimental result shows that the highest calorific value (≈ 7750 cal/g) was obtained at 450oC and 3h with charcoal characteristics: 2.75% water content, 2.70% ash content, and 9.50% volatile matter that meets the SNI requirements. The MLR analysis has justified that the effect of pyrolysis temperature is more dominant than pyrolysis time on almost all charcoal characteristics. The Lagrange polynomial interpolation shows the highest calorific value (≈ 7784 cal/g) obtained at 500oC and 3h. The finding applying MLR analysis and Lagrange polynomial interpolation based on experimental results is a new breakthrough in this investigation.